Representación Visual de los Monumentos del Cantón Ambato com o aporte a la Dirección de Cultura y Turismo del GAD Municipalidad de Ambato en el fomento de la pertenencia cultural - Duran Escobar, Dimitri Alexander (2024)
his integrative project is based on the visual representation of the monuments of the city of Ambato with the objective of promoting cultural belonging in the population from 15 to 19 years of age, based on observation cards to identify the location and condition of the monuments of the city and to be able to collect historical information about them with the support of the Directorate of Culture and Tourism of the GAD Municipality of Ambato, to make the proposal of the design of the visual representation of the monuments applying matte painting techniques for its use in multiplatform that empower the target audience and provide the emotional connection of a sense of pride and cultural belonging to the illustrious city of Ambato.